Variability of dermatoglyphic patterns in the third and the fourth interdigital areas of the palm - Buchwald, Wiesław (Anthropological Review, 1984)
Applying the folkwing system of classification: radial loop (W), ulnar kop (1,u), loop with a triradius (D), loop without a triradius (L), whorl (W) and area without a pattern (0) palm prints of 6117 males and 617 females lifving in Northern Poland were described. Two significant differerices. between sexes were found: in females lack of patterns in the third and fourth area is more frequent on the right hand th.an in males, while in males radial loop (Lr/10) is more irequent. Statistically significant differences between frequencies of patterns on right and left palms are marked with an asterisk in the tabie 1.